A Prospective Evaluation of Complications after Use of Exposed Pins in the Hand and Wrist. Issue 3 (September 2019) - Lutsky, Kevin F.; Edelman, David; Leinberry, Charles; Takei, T. Robert; Kwok, Moody; Gallant, Greg; Beredjiklian, Pedro
Abstract : Background: Kirschner wires are commonly used during hand surgical procedures. These pins are often left exposed (protruding from the skin) for ease of removal. Complications such as loosening, migration, or infection are not uncommon (ranging from 7 to 18 percent in current retrospective studies) and can compromise surgical outcome. This study evaluated the frequency of Kirschner wire–related complications. Methods: All patients who had Kirschner wires placed as part of their surgical procedure in the hand or wrist by one of 12 attending hand surgeons over a 6-month period were enrolled prospectively. Complications were recorded by the attending surgeon at follow-up visits. Demographics and patient comorbidities including diabetes mellitus and smoking history were recorded. Results: There were 141 patients enrolled and 230 pins used, including 65 women and 76 men. The mean age was 40.7 years. Thirteen patients were smokers, and eight had a history of diabetes. There were 35 soft-tissue procedures and 106 fractures. There were 35 complications (25 percent). There was a 12 percent rate of infection ( n = 17), including two cases of osteomyelitis. There were 18 other complications, nine of which were major complications (6.4 percent). Smoking, age, and location (hand/fingers versus wrist) were significantly associated with infection. Conclusions: In this study, one in four patients treated with Kirschner wires developed a minor or major complication, a rate that is substantially higher than reported in existing retrospective studies. Although Kirschner wires are often needed during hand surgery, surgeons should be aware that adverse events are frequent. Patients and surgeons should be vigilant in the perioperative period. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.